School democratization and social mobility in France: the empirical Sociology of Beaud, Truong and Pasquali (Práxis Educativa, 2020)
The article discusses recent developments in French Sociology on the classic themes of educational inequalities and social mobility. We analyse recent works by Stéphane Beaud, Fabien Truong and Paul Pasquali, which are at the crossroads of the Sociology of youth, education, immigration and social mobility. The authors address the trajectories in Higher Education of young individuals issued from popular classes through qualitative and longitudinal research. The article explains the theoretical and methodological foundations of these post-Bourdieusian studies and presents their main contributions to the contemporary sociological debate. We emphasise the breadth and density of the research; the analytical framework of social mobility when considering “class migration”; the construction of the research object, which inserts the theme of “school longevity” into the broader picture of the implications of displacements in the social space.Keywords: Working class youth. Higher Education. Social mobility.